Equations Reducible to Quadratic Section 11.5 Equations Reducible to Quadratic Phong Chau
Some equations are not quadratic, but can be turned into quadratic equation by using substitution. Such equations are called Equations in Quadratic Form or Reducible to Quadratic. x4 – 5x2 + 4 = 0 (x2)2 – 5(x2) + 4 = 0 u2 – 5u + 4 = 0.
Example Solve x4 – 5x2 + 4 = 0. Solution u2 – 5u + 4 = 0 Let u = x2. Then we solve by substituting u for x2 and u2 for x4: u2 – 5u + 4 = 0 (u – 1)(u – 4) = 0 Factoring Principle of zero products u – 1 = 0 or u – 4 = 0 u = 1 or u = 4
Check: Replace u with x2 TRUE TRUE x2 = 1 or x2 = 4 x = 1: x = 2: (16) – 5(4) + 4 = 0 (1) – 5(1) + 4 = 0 TRUE TRUE The solutions are 1, –1, 2, and –2.
Example Solve Solution u2 – 8u – 9 = 0 (u – 9)(u +1) = 0 Let u = . Then we solve by substituting u for and u2 for x: u2 – 8u – 9 = 0 (u – 9)(u +1) = 0 u – 9 = 0 or u + 1 = 0 u = 9 or u = –1
Check: x = 81: x = 1: FALSE TRUE The solution is 81.
Example Solve Solution u2 + 4u – 2 = 0 Let u = t −1. Then we solve by substituting u for t −1 and u2 for t −2: u2 + 4u – 2 = 0
Examples Solve the following equations: